Kardinal Cesare Baronio und das Kurienzeremoniell des posttridentinischen Papsttums Ein Beitrag zur Geschichte der römischen Kurie während der zweiten Hälfte des Cinquecento - Malesevic, Filip (De Gruyter, 2021)
This study embarks upon a new interpretation of the twelve-volume "Annales Ecclesiastici" by the Oratorian and cardinal Cesare Baronio within the context of the development of curial ceremony in the second half of the sixteenth century.